2018
DOI: 10.1016/j.idcr.2017.11.008
|View full text |Cite
|
Sign up to set email alerts
|

A recurrent hydatid cyst of the thigh diagnosed 13 years after initial presentation

Abstract: This case presents a hydatid cyst of the thigh in a 57-year-old patient born and raised in rural Montenegro. He presented with a painful erythematous mass on the lateral aspect of the right thigh at the site of a previous cystic mass resection 13 years earlier. Complete surgical resection was conducted, histopathology revealed laminated membranes and polymerase chain reaction was positive for Echinococcus granulosus. Primary musculoskeletal hydatidosis is a rare entity and diagnosis is challenging. Any cystic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…In this study, primary HC was found in the quadriceps compartment of the left thigh. Many reports in the literature list cases of hydatid disease in the adductors and quadriceps compartments of the thigh [ 4 , 5 , 7 - 14 ]. Most patients in such cases were females [ 4 , 5 , 7 - 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, primary HC was found in the quadriceps compartment of the left thigh. Many reports in the literature list cases of hydatid disease in the adductors and quadriceps compartments of the thigh [ 4 , 5 , 7 - 14 ]. Most patients in such cases were females [ 4 , 5 , 7 - 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many reports in the literature list cases of hydatid disease in the adductors and quadriceps compartments of the thigh [ 4 , 5 , 7 - 14 ]. Most patients in such cases were females [ 4 , 5 , 7 - 13 ]. The worm can remain dormant for an extended period of time (months to decades) without presenting any particular symptoms of hydatid disease [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current case reported positive history of animal contact without fulfilling any preventive measure. Up to date, 17 cases of HD of the thigh have been reported in the literature [ 2 , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] ]. The age ranged between 8 to 61 years [ 12 , 21 ].…”
Section: Discussionmentioning
confidence: 99%